CAM and Post-Traumatic Stress Disorder. Issue 1 (2007) - Hankey, Alex
Abstract : In the form of the Transcendental Meditation program CAM offers a method of eliminating deep-rooted stress, the efficacy of which has been demonstrated in several related studies. Any discussion of CAM and post-traumatic stress disorder should include a study of its application to Vietnam War Veterans in which improvements were observed on all variables, and several participants were able to return to work after several years of being unable to hold a job. The intervention has been studied for its impact on brain and autonomic nervous system function. It has been found to be highly effective against other stress-related conditions such as hypertension, and to improve brain coherence—a measure of effective brain function. It should be considered a possible 'new and improved mode of treatment' for PTSD, and further studies of its application made.